The Impact of Activation Patterns in the Explainability of Large Language Models – A Survey of recent advances - Figênio, Mateus R.; Santanché, André; Gomes-Jr, Luiz (Anais da Escola Regional de Banco de Dados (ERBD); 2024: Anais da XIX Escola Regional de Banco de DadosDO - 10.5753/erbd.2024.238868, 2024)
The performance benchmarks of Natural Language Processing (NLP) tasks have been overwhelmed by Large Language Models (LLMs), with their capabilities outshining many previous approaches to language modeling. But, despite the success in these tasks and the more ample and pervasive use of these models in many daily and specialized fields of application, little is known of how or why they reach the outputs they do. This study reviews the development of Language Models (LMs), the advances in their explainability approaches, and focuses on assessing methods to interpret and explain the neural network portion of LMs (specially of Transformer models) as means of better understanding them.